Academic Senate Minutes 2002-04-11 - Academic Senate:::::::::
Agenda and Minutes approved. Report from the Chair. Moment of silence for Fernando Nugent. Candidates for May 2002 graduation were accepted as a first reading. FSAC's substitute document for Evaluation of Temporary Faculty approved. Academic calendar motion from Structures & Functions accepted as a first reading. Reports from Provost, Associated Students, Chair-Elect, and EPC.